Evolution of the particle size distribution of tricalcium silicate during hydration by synchrotron X-ray nano-tomography. (June 2022) - Neubauer, J.; Sowoidnich, T.; Valentini, L.; Schulbert, C.; Naber, C.; Rößler, C.; DaSilva, J.; Bellmann, F.
Abstract: The particle size distribution of tricalcium silicate (C3 S) is essential for the modelling of early C3 S hydration kinetics. In this study, this parameter is analysed during the main hydration period until the first 20 h by synchrotron near-field ptychographic (NF-PXCT) and holographic (HXCT) computed nano-tomography. Additionally, X-ray diffraction, 29 Si NMR, thermal analysis, scanning electron microscopy, and inductively coupled plasma-optical emission spectroscopy were used to investigate the system evolution. The time-dependent pore solution composition is also provided to gain further information. HXCT and NF-PXCT show comparable values regarding the evolution of the C3 S particle size distribution during hydration, indicating that C3 S particles smaller than 1.3 μm are completely dissolved after 20 h of hydration. The results can be reasonably reproduced by numerical models if for all particle sizes a constant reacted rim thickness for each degree of hydration is assumed. Data on the aqueous phase composition are also provided.